Metacognitive-Based Learning Model: Improving Agile Innovation and Critical Thinking Skills of Students in Science Learning at Elementary Schools - I Gusti Ngurah Puger; Jian-Bang Deng; I Gede Wahyu Suwela Antara; Kadek Andre Karisma Dewantara; Made Sugiarta; Leonardo Veliz; Sudatha, I Gde Wawan; Sudarma, I Komang (Jurnal Pendidikan IPA Indonesia, 2024)
This research aims to analyze the influence of a metacognitive-based learning model on agile innovation and critical thinking abilities of students in science learning at elementary school level. The study population consists of fourth-grade students in elementary schools. The sample was selected using cluster random sampling with an intact group type in Bali. Participants in this research study are Grade 5 students in elementary schools in Bali Province, Indonesia. Samples were taken using a cluster random sampling technique with intact group type. Based on the sampling results, the experimental class comprised 32 students, who received pedagogical intervention in the form of metacognitive-based learning implementation, while the control class with 31 students was exposed to conventional learning models. A survey questionnaire was employed as data collection instrument. Data analysis included descriptive and inferential analysis. Based on the analysis of agile innovation data, an F-value of 23.994 was obtained with a significance value of 0.000 (<0.05). From these results, it can be concluded that there is a significant difference in agile innovation between students who experienced metacognitive-based learning and those who did not. The group of students who received metacognitive-based learning showed a higher level of agile innovation with an average score compared to the group of students who did not experience metacognitive-based learning. Additionally, data on critical reasoning abilities showed an F-value of 20.915 with a significance value of 0.000 (<0.05). In conclusion, there is a significant difference in critical reasoning abilities between students who received metacognitive-based learning and those who did not.